ANH in Complex Cardiac Surgery: A Prospective Randomized Study - Lorraine N. Lubin; Tiffany Williams; Sophia P. Poorsattar; Ravi C. Gadasally; Jonathan K. Ho; Tristan R. Grogan; Reed Harvey; Jure Marijic; Jacques D. Neelankavil (International Journal of Blood Transfusion, 2025)
Objectives Blood transfusions in cardiac surgery are associated with increased morbidity and mortality. The purpose of this study is to identify potential benefits of ANH in high-risk cardiac surgery. Design This was a prospective, randomized, controlled study. Setting The study was performed at a tertiary care university hospital. Participants 61 patients who underwent complex cardiac surgery with cardiopulmonary bypass (CPB) were enrolled in the study. Measurements and Main Results After randomization, 32 patients were assigned to the ANH arm, and 29 patients were assigned to the control group. ANH was associated with a lower incidence of total perioperative pRBC transfusion (0.6 ± 1.2 units vs 2.7 ± 6.8 units; p = 0.030/0.049). Total perioperative transfusion of all other fractionated blood products, including platelets (0.8 ± units vs 1.9 ± 2.4 units; p=0.010), cryoprecipitate (0.5 ± 0.7 vs 1.3 ± 2.0; p=0.016) and FFP (0.5 ± 1.0 vs 2.3 ± 6.2 units; p=0.013), was significantly lower in the ANH group compared to controls. Participants in the ANH group received significantly fewer intraoperative transfusions of pRBC (0.4 ± 1.2 vs 2.6± 7.0 units; p=0.037), platelets (0.8 ± 1.2 units vs 1.9 ± 2.4 units; p=0.013, logtrans), FFP (0.4 ± 0.9 vs 2.5 ± 6.4 units; p=0.003) and cryoprecipitate (0.5 ± 0.7 vs 1.3 ± 2.1 units; p=0.012, logtrans). With respect to secondary clinical outcomes, ANH participants had statistically shorter ICU (3.7 ± 1.9 vs 5.4 ± 3.6 days; p=0.020) and hospital (6.7 ± 2.1 vs 9.5 ± 7.7 days; p = 0.048) length of stays Conclusions ANH in complex cardiac surgical patients is safe and may be effective in reducing the allogenic blood product transfusion of PRBCs, FFP, platelets and cryoprecipitate in the perioperative period.
Keywords: acute normovolemic hemodilution